Household debt and economic growth in Asia Pacific / Fatin Nadira Roslim - Roslim, Fatin Nadira (Faculty of Business and Management, 2018)
Household debt does give impact towards the growth of economic. Higher in household debt is deemed to be at worrying stage as it could turn out lead to another financial crisis. Therefore, the study aims to investigate the relationship between household debt on economic growth in selected Asia Pacific countries. The variables used in this study including Household Debt (HD), Consumption (C ), Labor Force (LF), Gross Capital Formation (GCF), Unemployment Rate (U ) and Household Saving as independent variables and Gross Domestic Product (GDP) as dependent variable. Moreover, the study utilized the theory of Solow Growth Model to estimate the regression.